Razvoj postopkov in naprav za uporabo pri suhem obdelovanju - Kulekci, Mustafa Kemal (Strojniški vestnik, 2007)
In this study a recent development in the dry-machining process is discussed. Dry machining eliminates the problems of cutting-fluid contamination, disposal, filtrations and the risk of health problems. The suitability of the workpiece for dry machining depends on the material's properties. The performance of the cutting tool for the dry-machining process depends on the properties of the coating. The process also has a restriction that must be taken into consideration: the rapid, repetitive fluctuations of the temperature lead to expansion, contraction and an increased risk of thermal cracking of the cutting edge. The presence of the coolant exacerbates the thermal cracking problem. Dry machining keeps the tool hot and tougher. Duringthe dry-machining process the coating takes the place of the coolant in protecting the cutting edges from wear and ensures reliable chip evacuation. Additional studies are needed on the dry-drilling and taping process for long chipping materials.
Keywords: suha obdelava; rezalna orodja; prevleke